Caregiving for Patients Diagnosed with Ovarian Cancer: An Examination of Distress and Relationships with Healthcare Providers Using Attachment Theory - Petricone-Westwood, Danielle (Université d'Ottawa / University of Ottawa, 2020)
This thesis focuses on describing and investigating the experiences of caregivers of individuals with ovarian cancer. Caregivers are an essential part of cancer care, and yet they are not formally recognized as such. The special focus on these caregivers stems from the recognition that ovarian cancer is unique from more commonly studied diseases, with a poor prognosis and frequent recurrences. This thesis sought to study this understudied population. The thesis begins with a scoping review of existing literature that specifically investigated this population. From this study, it was confirmed that few studies had focused on this population, however the mapped literature suggested that these caregivers experienced significant compromises to their quality of life. Some preliminary studies identified a theme that the caregiving experience was influenced by the relationships with healthcare providers. This theme informed the second study of the thesis, that was a cross-sectional, correlational study that sought to recruit partner-caregivers of patients with ovarian cancer, a sample mostly of male-caregivers. This study sought to explore multiple facets of the caregiving experience as part of cancer care using the Cancer Caregiving Tasks, Consequences and Needs Questionnaire, measuring caregiver distress using the Hospital Anxiety and Depression Scale, and collecting sociodemographic and proxy-reports of the patient’s medical information. A total of 82 partner-caregivers were recruited for the study, and our sample were mostly men, White, affluent and highly educated. Most of their partners were diagnosed with stage III or IV disease, and were treated with both surgery and chemotherapy. This study’s analysis found that caregiving workload, lacking information from healthcare providers, problems with the quality of information and communication with healthcare providers, lacking time for social relations due to caregiving, and needing more help from healthcare providers correlated with distress outcomes. The third investigation sought to further explore these relationships by measuring attachment insecurity, as assessed by a short, modified version of Experiences in Close Relationships Scale. Using the same sample data, hierarchical regression analyses were used to test whether general attachment avoidance or attachment anxiety moderated the relationship between the caregiving experiences and distress outcomes. These analyses revealed that attachment anxiety contributed to a portion of the variance in distress, however the experiences with the healthcare team explained a large portion of the variance of distress. Attachment anxiety was found to play a minor role moderating the relationship between needing more help from healthcare providers and anxiety, and attachment avoidance contributed a very small, moderating role between lack of time for social relations and distress. Together, these studies have demonstrated that caregivers of patients with ovarian cancer are understudied, however they experience significant levels of depression and anxiety. Their distress is highly affected by their reported experiences as part of the cancer care team, regardless of their predisposition to distress through attachment insecurity.
Keywords: Ovarian Cancer; Caregivers; Relationships with Healthcare Proviers; Distress; Attachment Theory